ANALISIS KOEFISIEN ALIRAN PERMUKAAN PADA TIGA TIPE PENGGUNAAN LAHAN di TANAH ANDISOL - Ikasapta Ramehiang; Johan Rombang (Universitas Sam Ratulangi, 2018)
ABSTRACT Current changes in land use caused by population growth and development in the development sector are increasing. This has a significant impact on changes in surface flow values, causing the flow coefficient to increase resulting in flooding. One of the important concepts in efforts to control flooding is the surface flow coefficient or commonly represented by C. This number of surface flow coefficients is one indicator to determine whether a watershed has been disturbed (physically). This study aims to calculate the Surface Flow Coefficient (C) in the type of forest land use, shrub land and open land. The method in this study used a randomized block design as a data collection method which was then analyzed using analysis of variants. From the results of measurements carried out in the field, the coefficient of surface runoff of forest land and shrub land is significantly different from open land where in forest land is 0.0019 and shrub land has a value of 0.0013, while open land is 0.0036. From the results of measurements carried out in the field, the infiltration rate in a row is shrub land of 210 mm / hour, forest land of 99 mm / hour and open land of 69.6 mm / hour. Forest land has a smaller infiltration rate compared to shrub land because forest land in the study area is artificial forest planted with vegetation, strata and has a different root system of natural forest. Keywords: surface flow coefficient, infiltration, surface flow